Study of Dependence of the Mechanical Properties of Polydicyclopentadiene Irradiated with Electron and γ Radiation; Polymer Science, Series A; Vol. 63, iss. 1 - Kozhanova M. Yu. Mariya Yurjevna; Litvinenko O. V. Olga Viktorovna; Lyapkov A. A. Aleksey Alekseevich; Golubenko I. S. Igor Sergeevich (2021, 2021)
Title screen